Artificial Intelligence in Fintech: Transforming Financial Inclusion for Women Entrepreneurs - Jinal Vishal Lathia (Journal of Informatics Education and Research, 2025)
This study investigates the role of artificial intelligence (ai) in financial technology (fintech) and its impact on the financial inclusion of women entrepreneurs. It explores awareness, usage patterns, and the challenges faced in adopting ai-driven fintech tools. Primary data was collected through structured questionnaires and analyzed using statistical tests including chi-square, t-test, and correlation analysis. The findings suggest that while ai-fintech tools can significantly improve access to credit and financial decision-making, several barriers such as digital illiteracy, lack of awareness, and trust issues limit their adoption. The paper concludes with strategic recommendations for fintech developers, policymakers, and support organizations to enhance the inclusivity and accessibility of ai-powered financial services.